BOT-3 GENOME-WIDE ASSOCIATION STUDY OF INTRACRANIAL GERM CELL TUMORS: A COMMON DELETION ATBAK1 ATTENUATES THE ENHANCER ACTIVITY AND CONFERS RISK FOR THE BRAIN TUMORS IN CHILDREN ADOLESCENTS AND YOUNG ADULTS. (3rd December 2022) - Terashima, Keita; Sonehara, Kyuto; Kimura, Yui; Nakano, Yoshiko; Ozawa, Tatsuya; Takahashi, Meiko; Suzuki, Ken; Fujii, Takashi; Matsushita, Yuko; Tomiyama, Arata; Suzuki, Tomonari; Yamaguchi, Shigeru; et al.
Abstract: Intracranial germ cell tumors (IGCTs) are rare brain tumors that mainly occur in children, adolescents and young adults with a particularly high incidence in East Asian populations. The biological basis of these tumors is still largely unknown. We conduct a genome-wide association study (GWAS) of 133 patients with IGCTs and 762 controls of Japanese ancestry by using Infinium Asian Screening Array and other molecular biology methods. A common 4-bp deletion polymorphism in an enhancer adjacent to BAK1 is significantly associated with the disease risk (rs3831846; P = 2.4 × 10 −9, odds ratio = 2.46 [95% CI: 1.83-3.31], minor allele frequency = 0.43). Rs3831846 is in strong linkage disequilibrium with a testicular GCTs susceptibility variant rs210138. Expression quantitative trait locus (eQTL) analysis using the GTEx dataset reveals that the risk allele of rs3831846 has a down-regulating effect on BAK1 expression in a wide range of tissues. Further in-vitro reporter assays reveal rs3831846 to be a functional variant attenuating the enhancer activity. BAK1 is a pro-apoptotic member of the BCL-2 family, thus our results suggested that the risk allele may contribute to IGCTs predisposition through down-regulating BAK1 expression. Risk alleles of testicular GCTs derived from the European GWAS show significant positive correlations in the effect sizes with the Japanese IGCTs GWAS (P = 1.3 × 10 -4, Spearman's ρ = 0.48). Of the 57 loci, 11 exhibit significant association with IGCTs and these loci were implicated in a broad range of biological pathways, including KIT/KITLG signaling, apoptosis regulation, and telomerase activity. The risk allele frequency of rs3831846 is higher in east Asia than Europe (0.49 vs. 0.20), which may provide a partial explanation for the ethnic difference in incidence. Nevertheless, our results suggest the shared genetic susceptibility of GCTs beyond ethnicity and primary sites.